Danos morais no Brasil e punitive damages nos Estados Unidos e o Direito de imprensa - Souza, Wendell Lopes Barbosa de (2013)
It can be seen today the real tendency of the civil liability under Brazilian law to the American system of common law precedents, each one with its details. On the other hand, examining U.S. law, there is a proliferation of written statutes, which are parameters to the production of jurisprudence relating to the cases of compensation for punitive damages. In reality, despite being situated in the Brazilian legal system among those members of the labeled civil law, supported by robust written legislation, with regard to compensation for non-compensatory damages can be said without hesitation that the course of jurisprudence leads to the conviction that damage issues are today being resolved by decisions fixed to an eminently factual bases, which have relied on statements by the Judiciary. Consequently, the judicial cases, for example, involving the non-compensatory damage and its consequences, like the turbulent fixing quantum of money, are resolved exclusive under precedents for the fact identical or at least similar. In the United States, a country that adopted the system of precedents for the resolution of legal disputes, including, at first, the group of nations adept to common law, it is noticed today the contingency of the production of statutes for the discipline of relevant topics, as the issue of punitive damages, making room for the written law of legal rules guiding judicial decisions. Hence we speak in interface between civil law and common law regarding the judicial resolution of the cases that focus on issues relating to non-compensatory damages in Brazil and punitive damages in the United States in the press law, especially when the case is about the the press company s right to inform and the right of privacy of the news subject